Government and governance of security: the politics of organised crime in Chile - Solar, Carlos (Routledge studies in Latin American politics, 2018)
Understanding governance -- Security and organised crime -- Governance, policy networks and institutions -- Governance in Chile -- Dealing with post-authoritarian governance -- New actors and criminal threats -- Networks for policy-making -- The governance of security